2006
DOI: 10.1007/s00037-007-0218-9
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorandomness for Approximate Counting and Sampling

Abstract: Abstract. We study computational procedures that use both randomness and nondeterminism. The goal of this paper is to derandomize such procedures under the weakest possible assumptions. Our main technical contribution allows one to "boost" a given hardness assumption: We show that if there is a problem in EXP that cannot be computed by poly-size nondeterministic circuits then there is one which cannot be computed by poly-size circuits that make non-adaptive NP oracle queries. This in particular shows that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Klivans and van Melkebeek [244] observed that the Impagliazzo-Wigderson pseudorandom generator construction is "black box" and used this to show that AM can be derandomized using functions that are worst-case hard for circuits with an NP oracle (Theorem 7.68). Subsequent work showed that one only needs worst-case hardness against a nonuniform analogue of NP ∩ co-NP [289,356,357].…”
Section: Chapter Notes and Referencesmentioning
confidence: 99%
“…Klivans and van Melkebeek [244] observed that the Impagliazzo-Wigderson pseudorandom generator construction is "black box" and used this to show that AM can be derandomized using functions that are worst-case hard for circuits with an NP oracle (Theorem 7.68). Subsequent work showed that one only needs worst-case hardness against a nonuniform analogue of NP ∩ co-NP [289,356,357].…”
Section: Chapter Notes and Referencesmentioning
confidence: 99%
“…PRGs for non-deterministic circuits can be constructed if we require that the function h cannot be computed by non-deterministic circuits [KvM02,SU06]. Such PRGs are useful for derandomizing the class AM of "Arthur-Merlin protocols" [KvM02,MV05,SU05,SU06] and are also useful in other contexts (as we see later on).…”
Section: Assumption 1 (Nw Hardness Assumption) There Is a Boolean Funmentioning
confidence: 99%
“…Another resource-bounded measure result regarding P/poly is a conditional one: Köbler and Lindner [40] showed that if µ p (NP) = 0, then P/poly has measure 0 in EXP NP . The full version of [35] uses derandomized approximate counting [70] to improve this to dim(P/poly | E NP ) = 0 under the same hypothesis. Is there a small span theorem for dimension?…”
Section: Circuit-size Complexity Imentioning
confidence: 99%